Inter-organizational conflict and construction project performance: Influencing mechanism based on trust networks - Xiang Wang; Yilin Yin (PLoS ONE, 2025)
Research on inter-organizational conflicts among the participants of construction projects typically concentrate on the binary perspective of the project owner and contractor, disregarding the correlation of the complex relationship networks on conflict incidents. This research will propose a systematic set of strategies for reducing inter-organizational conflicts and enhancing project performance from the perspective of trust networks governance. Specifically, the research aims to uncover the interactive mechanisms among the trust network of all participants in construction projects, inter-organizational conflicts, and project performance, thereby filling the existing research gaps. The PLS-SEM approach was employed to analyze 207 valid questionnaires from the participants of construction projects. Data analysis revealed that both the density and stability of the trust networks can restrain various forms of inter-organizational conflicts, and inter-organizational conflicts can impede the attainment of project performance. The density of trust networks can enhance project performance, yet the extent to which the stability of network structure is related to this aspect remains unproven. These findings are conducive to optimizing the performance level of engineering projects and reducing the probability of inter-organizational conflicts.